Global before birth: A study of internationalization mindsets of entrepreneurs. Issue 2 (3rd April 2023) - Costa, Sílvia; Frederiks, Arjan J.; Englis, Paula D.; Englis, Basil G.; Groen, Aard J.
ABSTRACT: Our research finds that even before a start-up has formed, a combination of the entrepreneur's willingness and ability to internationalize determines the likelihood that an entrepreneur will in fact internationalize. Even before a venture is launched, entrepreneurs already have an internationalization mindset that influences their engagement in internationalization activities later on in the entrepreneurial process. Two hundred and thirteen early-stage entrepreneurs in a business accelerator participated in this research. Using intake data, we mapped their entrepreneurial internationalization mindset profiles. Two years after intake, we observed the actual internationalization behavior of the firms. We discuss the implications of our research for entrepreneurship policy makers, support organizations, business accelerators, and entrepreneurs.